2014
DOI: 10.1002/ajpa.22570
|View full text |Cite
|
Sign up to set email alerts
|

The ontogeny of nasal floor shape variation in extant humans

Abstract: Variation in nasal floor topography has generated both neontological and paleontological interest. Three categories of nasal floor shape (Franciscus: J Hum Evol 44 (2003) 699-727) have been used when analyzing this trait in extant humans and fossil Homo: flat, sloped, and depressed (or "bi-level"). Variation in the frequency of these configurations within and among extant and fossil humans has been well-documented (Franciscus: J Hum Evol 44 (2003) 699-727; Wu et al.: Anthropol Sci 120 (2012) 217-226). However,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(49 citation statements)
references
References 24 publications
1
48
0
Order By: Relevance
“…Further, Smith et al () suggest that pneumatization into particular processes may be limited to certain developmental windows, during which lack of spatial availability may permanently restrict future sinus expansion. Importantly, several studies on regional variation in human facial ontogeny (Viðarsdóttir et al, ; Viðarsdóttir and O'Higgins, ; Sardi and Rozzi, ; Nicholas and Franciscus, ; Freidline et al, ) have shown that differences in basic spatial dynamics seen in adult facial morphology appear early during ontogeny. Accordingly, our results may suggest that adult humans with large (i.e., tall) zygomaticomaxillary interfaces possess sinuses that extend further into the zygomatic process of the maxilla (or even into the zygomatic) because these individuals possess sufficient space for pneumatization to occur in the area during particular periods of their growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…Further, Smith et al () suggest that pneumatization into particular processes may be limited to certain developmental windows, during which lack of spatial availability may permanently restrict future sinus expansion. Importantly, several studies on regional variation in human facial ontogeny (Viðarsdóttir et al, ; Viðarsdóttir and O'Higgins, ; Sardi and Rozzi, ; Nicholas and Franciscus, ; Freidline et al, ) have shown that differences in basic spatial dynamics seen in adult facial morphology appear early during ontogeny. Accordingly, our results may suggest that adult humans with large (i.e., tall) zygomaticomaxillary interfaces possess sinuses that extend further into the zygomatic process of the maxilla (or even into the zygomatic) because these individuals possess sufficient space for pneumatization to occur in the area during particular periods of their growth and development.…”
Section: Discussionmentioning
confidence: 99%
“…The current study confirms the results of work by Mooney & Siegel (1986a,b) and Weinberg et al (2005) that showed population variation in maxillary traits developing, in some cases, prenatally. While not all maxillary traits that vary by population follow this pattern (such as the internal nasal floor, see Nicholas & Franciscus, 2014), there is sufficient shape variation at these young ages for it to be easily quantified using a relatively restricted set of coordinate landmarks. Geometric morphometric methods' ability to quantify continuous variation, along with variation that may be more difficult to parse due to the physically small size of fetal material, may help to increase accuracy when trying to estimate ancestry for fetal or neonatal individuals.…”
Section: Discussionmentioning
confidence: 99%
“…Generalized Procrustes analysis (GPA) was performed to translate, rotate, and scale the landmark configurations of each subject (Mitteroecker, Gunz, Windhager, & Schaefer, ; Rohlf & Slice, ). The role of allometry was assessed by regressing all Procrustes‐aligned shape coordinates on centroid size (Adams, Collyer, & Sherratt, ; Drake & Klingenberg, ; Mitteroecker et al, ; Nicholas & Franciscus, ). This process allowed an assessment of the statistical relationship between shape and size within each age point.…”
Section: Methodsmentioning
confidence: 99%